A PROPOSAL FOR IOF AND ICMS REFORM AND ITS IMPACTS ON THE BRAZILIAN TAX SYSTEM (REMUNOM, 2025)
This article begins by addressing the need to rethink the Brazilian tax system, particularly in light of persistent social and economic inequalities. It proposes a critical analysis of two high-impact taxes—IOF (Tax on Financial Operations) and ICMS (Tax on Circulation of Goods and Services) comparing them with international experiences that adopt simpler, more efficient, and fairer models. The study aims to understand how these taxes directly affect the population, with an emphasis on poorer classes who bear a disproportionate tax burden relative to their income. The methodology involves a bibliographic review of classical and contemporary authors in economics and public administration, complemented by statistical data from institutions like IPEA. The main objective is to present a tax reform proposal for the restructuring of IOF and ICMS, focusing on simplification, transparency, and fiscal justice. The article discusses how the current structure of these taxes is complex, outdated, and often ineffective in promoting equity and stimulating economic activity. Additionally, examples of international best practices are presented as inspiration for Brazil, reinforcing the idea that it is possible to balance revenue collection and social justice. The text provides a detailed analysis of how these taxes function, their critical points, and practical suggestions for improvement. Finally, the proposed reform seeks to contribute to the debate on modernizing the national tax system, offering viable and sustainable alternatives for a fairer and more efficient model.